Analisis Analisis Berpikir Kritis Siswa SMP dalam Menyelesaikan Soal Pecahan ditinjau dari Gaya Belajar - Muslimah, Ayu Imamatul (Department of Mathematics Education , University of Jember, 2020)
In learning activities, one of the efforts that can be done to improve students' learning abilities is to support learning styles that are following the objectives so that learning can be done effectively. This research was conducted at Junior High School 1 Kalisat, located at Jl. Diponegoro 52 Kalisat, Jember. This study aims to describe the students' critical thinking processes in solving fraction problems in terms of visual, auditory and kinesthetic learning styles. Data collection techniques used consisted of learning style questionnaires, critical thinking tests, and interview method. The subjects in this study were 6 students consisting of 2 students who represented visual, auditory, and kinesthetic learning styles. Based on data analysis, the results show that students with a visual and kinesthetic learning style meet five indicators of critical thinking, namely basic clarification, basic skills, concluding, further clarification, and strategies and tactics. Students with auditory learning styles meet the four indicators of critical thinking namely basic clarification, building basic skills, further clarification, and concluding. While students with auditory learning styles are less able to meet the indicators of strategies and tactics. Keywords: Critical Thinking, Learning Styles, Fraction Problems